Assessing hatching rates and the timing of hatching from plankton resting stages—an accurate and cost effective high throughput approach. (8th July 2016) - Czypionka, Till; Reeves, Guy; Vanhamel, Matthias; De Meester, Luc
Abstract: Hatching rates and the timing of diapause termination are traits of high relevance in ecology and evolution of diapausing organisms. The analysis of hatching from dormant stages of planktonic organisms is an active area of research, which has been extensively studied in the context of phenology adjustment over latitude. Research on populations from temporary ponds has revealed temporal hatching profiles consisting of various hatching peaks, which is considered a risk‐spreading strategy. Studies on outstanding scientific questions such as the evolution of risk‐spreading strategies, the importance of genetic variation in hatching in an eco‐evolutionary context, and the genomic underpinning of hatching phenotypes all require very large sample sizes. We therefore developed a high throughput approach for the assessment of hatching rates and temporal hatching profiles of resting stages from crustacean zooplankton. Our method consists in the photographic monitoring of resting stages hatching assays and the detection of hatchlings using free software for the automation of biological image analysis. We compared the performance of our new method with data obtained by traditional visual assessment of hatching. Our results indicate that our approach is highly accurate (>95%) and raises efficiency by a factor of 10 compared to non‐automated visual assessment. Our new high throughput approach therefore allows to upscale the analysis of temporal hatching profiles and hatching success to sample sizes that will enable large‐scale genomic studies or massive phenotyping and monitoring of these highly relevant traits in the future.